Preservação digital nas Ciências da Saúde: modelo de metadados para preservação do prontuário eletrônico do paciente - Sales, Odete Máyra Mesquita (2022)
Considering the need to safeguard the memory of health, this thesis is based on the idea that the creation of a specific metadata model, focused on the digital preservation of electronic patient records, will contribute to the access and use of information. Besides collaborating to improve the search and retrieval of health documentation, which will enable greater completeness of data, interoperability of systems, and preservation of the memory of health. Therefore, the main objective of the research was to build a metadata model for the digital preservation of electronic patient records, with a view to optimizing access to and use of information, as well as safeguarding the memory of health care. The choice of the theme is motivated mainly by the need to create a metadata scheme for electronic patient records that aims to preserve the data contained in these documents, favoring the access and retrieval of health information in the Medical Archives and Statistics Service. The theoretical framework addresses the impact that Digital Information and Communication Technologies have on Information Science and Health Sciences, highlighting the relationship between these areas, to enter the theme of Digital Preservation and patient records. The research is characterized as applied, exploratory, descriptive and propositional, anchored in the quadrupole method, from a qualitative approach that gave us support for the development of the metadata model for digital preservation focused on electronic patient records. The empirical study was developed at the Medical Archives and Statistics Service of the Walter Cantídio University Hospital of the Federal University of Ceará. The corpora of the research fell on two patient records, one analog and the other digital. The analyses indicate that it is possible to use the digital preservation standards existing in the literature as a basis for the definition of minimum metadata for preservation applied to the context of patient records. We conclude by presenting a metadata model for digital preservation of electronic patient records that differs from the models addressed in the literature, meeting the conditions with respect to the record and with the purpose of ensuring that the information remains available, retrievable and understandable.